Russia's Output Collapse and Recovery : Evidence from the Post-Soviet Transition - Kvintradze, Eteri (IMF Working Papers; Working Paper ;, 2010)
The health of the Russian economy still depends heavily on natural resource revenues. The history of the economic collapse and recovery in 1970-2004 provides new evidence on the sources of Russian economic growth, while a survey of the economic literature suggests that the Russian economy could be viewed as a weighted combination of virtual and normal forces. If the Russian economy is considered to be dominated by normal market economy forces, higher energy export receipts provide an opportunity for structural reforms while compensating for social costs, making the economy less vulnerable to decline in world energy prices. However, the domination of virtual forces-value transfers from the energy sector to strategic enterprises-suggests that high world energy prices are masking an inefficient manufacturing sector, and that the Russian economy is highly vulnerable to energy price declines.